(untitled) (Global Journal of Management and Business Research, 2013)
In most of the organizations the human resource counselors, professionals and managers are concerned about the impact of job satisfaction and organizational commitment. However, many academic institutions have very little understanding of how job satisfaction affects employee’s turnover, productivity and organization’s performance. There-fore it is essential to understand the causes, symptoms and the effect it has. The main objective of the present paper is to study the job Satisfaction and Organizational Commitment of faculty members in Technical and Management Institutes with reference to different institutes in Dar es Salaam region. For this purpose the data was collected through questionnaire under convenience random sampling of Management and Technical faculty members. The analysis has been done using different Statistical tools with the help of SPSS. The findings reveal and demonstrate that dissatisfaction does exist in the academic organizations/institutions, which eventually results to decrease of organizational commitment. Thus, the managers of various organizations should come up with various interventions to manage the dissatisfaction among the faculty members.